Adaptive Translational Regulation in Response to Low-Dose Gamma Irradiation in HFL1 Lung Fibroblasts - Tamaddondoust, Rosette Niloufar (Université d'Ottawa / University of Ottawa, 2025)
Understanding the cellular responses to low-dose ionizing radiation (IR; ≤ 0.1 Gy) is essential for developing evidence-based radiation protection policies. While the effects of high-dose IR on gene expression and protein synthesis are well documented, how cells selectively remodel their gene expression under low-dose IR stress remains poorly understood. To address this gap, I performed ribosome profiling on normal human lung fibroblast cells exposed to low (0.1 Gy) and high (1 Gy) doses of ⁶⁰Cobalt gamma (γ) rays. At 1 and 6 hours post-irradiation, the results demonstrate that while low-dose IR does not significantly change global protein synthesis, subsets of mRNAs show distinct increases or decreases in translation efficiency. These translational changes contrast with minimal alterations observed at the transcriptional level following low-dose exposure. The data suggest that specific biological processes are modulated upon low-dose γ-radiation. The small GTP-binding protein RAB33B was identified as a translationally upregulated target in response to IR. This study emphasizes that conventional transcriptome analyses do not fully capture gene expression dynamics in response to low-dose IR exposure. Moreover, I identify dose-rate as a confounding factor, highlighting the importance of considering both dose-rate and cumulative dose in experimental design. Understanding the features that govern preferential mRNAs translation or repression in response to γ irradiation may offer deeper insights into the subtle adaptive responses to common low-dose radiation exposures from the environment, medical devices, or occupational activities.
Keywords: low dose radiation; adaptive response; stress; translation; protein synthesis